Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-22 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Comparison between development and the repair of an almost complete cervical spinal cord injury upon one year (A,C,G) (therapy started at an age of 15.5 years) and 5 years of coordination dynamics therapy (B,E,H) (CDT started with 17 years). The MRI of the SCI of the patient of the left panel is shown in 'I' and those one of the right panel in 'K'. Trunk rotation (A,B,C), un-sustained sitting (D,E,F), and four-point kneeling (G,H,I) is compared between one year and 5 years of CDT and with the positioning of an infant.